Features of formation and accounting of registered (share) capital for enterprises of various organizational and legal forms - I. Kosata; O. Diahileva; A. Peredera (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
The accounting of registered capital is a crucial aspect of the financial activities of any company. It determines its financial potential, influences its creditworthiness, and attractiveness to investors. A profound understanding of the processes of formation and accounting of registered (equity) capital not only ensures the reliability of financial reporting but also serves as a factor in managerial resources, strategic planning, and attracting investments for further development. This article discusses the peculiarities of forming registered (equity) capital by components according to the characteristics of different legal entities and forms of ownership. It reflects the definition of registered (equity) capital according to IFRS and other legislative documents. A detailed description of the subaccounts of account 40 "Registered (Equity) Capital" is provided, including statutory, payment, and other registered capital. Various types of economic entities are identified and characterized: joint-stock company, limited liability company, additional liability company, general partnership, and limited partnership. The difference between the concepts of statutory, registered, equity, and other registered capital is outlined. Legislative regulation of the creation and amendments to registered capital is highlighted. Founding documents, minimum initial contribution size, minimum statutory capital size, line for initial external capital injection, and maximum term for forming statutory capital are reflected for each organizational and legal form. Special attention is paid to the accounting of registered (equity) capital, considering its components in the context of the formation of economic entities with all organizational and legal forms and forms of ownership. The article thoroughly analyzes the principles and methodology of accounting for registered capital for different types of organizations and provides examples of the most common transactions related to the creation and accounting of registered capital. Clear definitions of requirements and standards regulating this process are also provided.